Potensi Penggunaan Blockchain dalam Pengembangan Sistem Moneter Islam yang Inklusif dan Berkeadilan: Studi Pustaka - Ganjar Santika; Agus Sahroni; Arif Syaripudin (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2025)
Amidst the dynamic global economy that is often characterized by inequality, the development of an inclusive and equitable Islamic monetary system is a crucial urgency. An Islamic monetary system based on sharia principles and values can offer a promising alternative. In this context, blockchain can be utilized as a transformative technological innovation that can be aligned with the Islamic monetary system. This research utilizes a comprehensive literature review methodology from scientific journals and related books. This literature study analyzes the use of blockchain in the development of an inclusive and equitable Islamic monetary system, exploring the alignment of principles, potential applications and implementation challenges and implications. The findings of this study show that the core characteristics of blockchain such as decentralization, transparency, immutability and cryptographic security are aligned with the objectives and philosophical foundations of Islamic macroeconomics, such as the prohibition of riba, gharar, maysir, fairness of wealth distribution and financial inclusion. Potential applications include developing the efficiency of zakat, waqf and alms, issuing digital sukuk and developing Islamic crowdfunding. Although the opportunities are wide open, the implementation still faces significant challenges, such as sharia compliance issues related to digital volatility, fatwa fragmentation, scalability issues, data security, consumption of shariah-compliant digital assets, and the need for digitalization.